Diseases of the spiritual heart as root causes of moral decay and corruption of justice based on imam al-Ghazali’s analysis - Hassan, Mohd. Kamal (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The paper argues based on the analysis of Imam Al-Ghazali that the major cause of moral decadence in the society today is as a result of non-purification of the diseases of the heart. It makes an analytical exposition of the term Ulu’l-Albab, i.e. men of Intellect as used by the Qur’an to show those men are of high moral standards. Thus, a purified soul will be of moral quality thus reducing corruption and moral decadence in the society.